Inflammatory Wnt5A signalling pathways affecting barrier function of human vascular endothelial cells - Tom Skaria; Gabriele Schoedon (BMC, 2017)
Abstract Wnt5A is a chemokine secreted by inflammatory-activated human macrophages that sustains their inflammatory response in an autocrine manner. High levels of Wnt5A are found in sera of patients with sepsis and septic shock. Here, we comment on recently reported Wnt5A signalling pathways in human vascular endothelial cells (VEC). In human VEC, Wnt5A regulates cytoskeleton remodelling and barrier function through Ryk receptor and Rho-associated protein serine/threonine kinase, targeting LIMK2 and CFL1 involved in actin polymerisation. Wnt5A/Ryk signalling in VEC can be antagonised by the naturally occurring Wnt inhibitory factor (WIF)-1 (WIF1). Therapeutic targeting of this mechanism may reduce vascular leakage and edema in severe systemic inflammation and therefore should be subject of further investigations.